IFPRI Malawi monthly maize market report, March 2025 - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
Highlights MARCH 2025 Retail prices of maize declined on average by 25 percent in March thanks to the arrival of newly harvested maize on the market. The depreciation of the Malawi kwacha against neighboring currencies at the informal exchange rates used for most cross-border maize trade slowed down in March, which further eased pressure on prices. Imports of old maize from Tanzania were increasingly complemented by new maize coming in from Mozambique and southern Zambia. By the end of March, imports dominated exports at nearly all border crossings.